Designed-in and contingent scaffolding in the Teaching Practice Groups model - Mallows, David (Indonesian Journal of Applied Linguistics, 2019)
The focus of this paper is the teacher learning of trainee teachers of English as a second, other or foreign language to adults, within a particular model of initial teacher training: Teaching Practice Groups. It draws on socio-constructive theories of teacher learning to explore the learning of trainees within the model. Teaching Practice Groups are highly social; trainees on courses using the model interact a great deal with each other, with their peers, with the learners in the teaching practice classroom, and also with the course documentation and activities. This paper suggests that these interactions, and the consequent development of trainees’ knowledge and understanding of teaching, are scaffolded in both ‘designed-in’ and ‘contingent’ ways (Hammond Gibbons 2005: 12). Designed-in scaffolding can be seen in the way the course is structured, in the activities that learners are expected to engage with, and in the documents and processes through which these processes are managed. Contingent scaffolding on the other hand, the spontaneous actions and guidance of the trainer in response to the immediate learning needs of the trainee teacher, is unplanned. While the findings from this study are specific to the context of Teaching Practice Groups, this paper also offers a contribution to more general knowledge about initial teacher training for English language teachers.